Punishing Neighborhood "Outsiders": Neighborhood Punishment Rates and the Spatial Mis(match) Between Defendants’ Residence and Arrest Locations - Johnson, Oshea (Crime & delinquency, 2024)
This study examines how ?outsider? arrests (i.e., arrests that happen in neighborhoods where defendants do not reside) and other covariates impact community-level punishment outcomes. Using census tract-level data on drug, violent, and property crime arrests occurring in Miami- Dade County (Florida) between 2012 and 2015, we estimate negative binomial regression models across three key punishment stages (pretrial detention, conviction, incarceration). Our findings suggest neighborhoods with higher levels of ?outsider? cases, concentrated disadvantage, and Black defendants experience significantly higher rates of pretrial detention, conviction, and incarceration, net of controls. These findings vary across crime types, implying that such factors may also shape court actors? focal concerns regarding neighborhood outsiders and other demographic factors. We discuss implications and directions for future research.